Pemeriksaan Kesehatan Gratis pada Lansia di Dusun Pungkit Loka B Kecamatan Lape - Herni Hasifah; Hamdin Hamdin; Rafi’ah Rafi’ah (Pusat Riset dan Inovasi Nasional, 2023)
Degenerative disease is a disease that is often suffered by the elderly. Degenerative disease is a disease caused by decreased organ function. Some of the degenerative diseases that many elderly suffer are hypertension, coronary heart disease, diabetes mellitus, gout, etc. This activity was held in June 2023 in Pungkit Loka B Village, Lopok District and was carried out door to door. This activity is carried out by conducting free health checks in the form of checking blood pressure, checking blood sugar, cholesterol and uric acid in the elderly. Based on the results of health examinations in the elderly, blood pressure was in the moderate category (54.2%), blood sugar levels were in the diabetes category (50%), cholesterol levels were in the rather high category (41.7%) and uric acid levels were in the high category (75%). Community service activities have been carried out well and smoothly